Nutritional management in newborn babies receiving therapeutic hypothermia: two retrospective observational studies using propensity score matching - Gale,C; Jeyakumaran,D; Battersby,C; Ougham,K; Ojha,S; Culshaw,L; Selby,E; Dorling,J; Longford,N (Health Technology Assessment, 2021)
BACKGROUND: Therapeutic hypothermia is standard of care for babies with moderate to severe hypoxic-ischaemic encephalopathy. There is limited evidence to inform provision of nutrition during hypothermia. OBJECTIVES: To assess the association during therapeutic hypothermia between (1) enteral feeding and outcomes, such as necrotising enterocolitis and (2) parenteral nutrition and outcomes, such as late-onset bloodstream infection. DESIGN: A retrospective cohort study using data held in the National Neonatal Research Database and applying propensity score methodology to form matched groups for analysis. SETTING: NHS neonatal units in England, Wales and Scotland. PARTICIPANTS: Babies born at ≥ 36 gestational weeks between 1 January 2010 and 31 December 2017 who received therapeutic hypothermia for 72 hours or who died during treatment. INTERVENTIONS: Enteral feeding analysis - babies who were enterally fed during therapeutic hypothermia (intervention) compared with babies who received no enteral feeds during therapeutic hypothermia (control). Parenteral nutrition analysis - babies who received parenteral nutrition during therapeutic hypothermia (intervention) compared with babies who received no parenteral nutrition during therapeutic hypothermia (control). OUTCOME MEASURES: Primary outcomes were severe and pragmatically defined necrotising enterocolitis (enteral feeding analysis) and late-onset bloodstream infection (parenteral nutrition analysis). Secondary outcomes were survival at neonatal discharge, length of neonatal stay, breastfeeding at discharge, onset of breastfeeding, time to first maternal breast milk, hypoglycaemia, number of days with a central line in situ, duration of parenteral nutrition, time to full enteral feeds and growth. RESULTS: A total of 6030 babies received therapeutic hypothermia. Thirty-one per cent of babies received enteral feeds and 25% received parenteral nutrition. Seven babies (0.1%) were diagnosed with severe necrotising e